Testing the strength of concrete made from raw and dispersion-treated concrete recyclate by addition of additives and admixtures - Stehlík, Michal (Journal of Civil Engineering and Management, 2013)
Today, concrete comprises more than 65% of the total volume of building constructions. As it undergoes degradation and buildings require refurbishment, the volume of concrete increases at disposal sites. Due to a lack of non-renewable resources and due to high prices of energies, the reuse of concrete seems to be more than desirable. It is common knowledge that in concretes made from recycled concrete, the strengths of the original concretes can hardly be achieved. The addition of dispersion additives and mineral admixtures into the freshly mixed concrete can contribute to improving the mechanical properties of concretes made from recycled concrete. Potential composite action of the recyclate, mineral admixtures and dispersion additives in increasing the compressive strength of concretes made from recycled concrete remains to be a question.